INTRODUCING YOU TO THE UNIVERSITY HOSPITAL OF OSTRAVA - Oborny, Tomas (Biomedical papers, 2007)
Historically, establishment of a medical facility inOstrava dates from 14th August 1912 when the municipalitiesof Vitkovice and Zabreh nad Odrou opened a jointlybuilt but not very large Epidemiological Hospital.The hospitalthen underwent developments which were infl uencedby two world wars and the social and political events ofthe past century. A new step in its mission was achievedwith a decision of the Ministry of Health to grant it thestatus of a University Hospital on 8th April 1992.
Keywords: UNIVERSITY HOSPITAL OF OSTRAVA